Hybrid analytical hierarchy process model for supplier selection - Sevkli, Mehmet; Lenny Koh, S.C; Zaim, Selim; Demirbag, Mehmet; Tatoglu, Ekrem (Industrial management + data systems, 2008)
Purpose - This paper aims to propose a new approach called "analytical hierarchy process weighted fuzzy linear programming model (AHP-FLP)" for supplier selection.Design methodology approach - A hybrid method of supplier selection, AHP-FLP is applied to a real industry case. The weights of the various criteria, taken as local weights from a given judgment matrix, are calculated using analytical hierarchy process (AHP) that are also considered as the weights of the fuzzy linear programming model. This new model is compared with the classical AHP method.Findings - This study concluded that the AHP-FLP method outperforms the AHP method for supplier selection with respect to restricted supplier selection criteria. Drawing on a real case, Supplier 1 was identified to be the best supplier through the AHP model under no restrictions, which contradicts the finding that Supplier 2 was selected as the best supplier by the AHP-FLP model subject to constraints.Research limitations implications - More research is definitely called for within the context of studying a more complex supply chain with multiple supply network and nodes. There is also a crucial need for investigating other hybrid methods to find the optimum supplier.Practical implications - The findings of this study indicate that the weights of supplier selection criteria calculated by the AHP-FLP model are in line with the actual supplier selection decision of purchasing managers. Since the AHP-FLP model is relatively more difficult to implement compared with the crisp AHP, its application will be more appropriate for high-value components where stringent purchasing criteria are required. In contrast, AHP remains an appropriate approach for relatively lower value components (C class).Originality value - The novelty of this study lies in the application of a hybrid approach to a real industry case. This study has dealt with one of the most important subjects in supply chain management, providing a better decision for supplier selection using appropriate quantitative techniques.